The Affective Scaffolding of Grief in the Digital Age: The Case of Deathbots. - Fabry, Regina E.; Alfano, Mark (Topoi: An International Review of Philosophy, 2024)
Contemporary and emerging chatbots can be fine-tuned to imitate the style, tenor, and knowledge of a corpus, including the corpus of a particular individual. This makes it possible to build chatbots that imitate people who are no longer alive — deathbots. Such deathbots can be used in many ways, but one prominent way is to facilitate the process of grieving. In this paper, we present a framework that helps make sense of this process. In particular, we argue that deathbots can serve as affective scaffolds, modulating and shaping the emotions of the bereaved. We contextualize this affective scaffolding by comparing it to earlier technologies that have also been used to scaffold the process of grieving, arguing that deathbots offer some interesting novelties that may transform the continuing bonds of intimacy that the bereaved can have with the dead. We conclude with some ethical reflections on the promises and perils of this new technology.